Tradition And Modernity In Contemporary Architecture Of Turkey (Comparative Study Referring To Traditional And International Architecture In 1940-1980) - Hassanpour, Naser; Soltanzadeh, Hossein (The Turkish Online Journal of Design Art and Communication, 2016)
There are a lot of similarities in contrast between tradition and modernity in contemporary architecture of Islamic countries in twentieth century affected by internal factors and international influences. In mentioned years which coincided years after Atatürk's death till the most important contemporary military coup in Turkey, governmental supports of each one of tradition demander and modernist have been accompanied with some internal and external factors in some periods and the contrast of mentioned tendencies forms the contemporary architecture in Turkey. In addition to the identification and classification of Turkey contemporary architecture tendencies and their social and political backgrounds, through investigating each one of tendencies’ outstanding architectural monuments, this article is sought to investigate how these works are affected by traditional or international architecture. The ideas of architecture and urban planning famous experts of Turkey have been used for studying and classifying the works or mentioned tendencies and in order to analyze the samples, reliable and diverse sources and field observations have been used. In addition to classifying Turkey contemporary architecture tendencies in mentioned year in three general sub-categories and introducing indicator works of each one of mentioned tendencies, the results of research compare their effectiveness of traditional and international architecture.
Keywords: contemporary architecture; Turkey; traditional architecture; international architecture